2010
DOI: 10.1007/s11060-010-0334-2
|View full text |Cite
|
Sign up to set email alerts
|

High dose methotrexate for pediatric high grade glioma: results of the HIT-GBM-D Pilot study

Abstract: We conducted a phase II study to test methotrexate (5 g/m(2)), as a single agent prior to radiochemotherapy for pediatric high-grade glioma and diffuse intrinsic pontine glioma. Thirty patients (19 male, median age 10.8) were enrolled. Tumors were located as follows: cortex 10, pons 7, other 13. Tumor resection was classified as gross total in 6, subtotal in 6, partial in 4, biopsy in 11 and not performed in 3. WHO grading of the histology was: IV: 11, III: 12 and II: 3. Patients received methotrexate 5 g/m(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 32 publications
1
23
0
3
Order By: Relevance
“…19 HIT-GBM-B -treated participants with RT and concurrent chemotherapy (cisplatin/etoposide in the first cycle and cisplatin/ etoposide/ifosfamide in the second cycle) followed by interferon-g and/or low-dose cyclophosphamide maintenance therapy 20 ; HIT-GBM-C involved administration of intensive chemotherapy (vincristine, cisplatin, ifosfamide, and etoposide) both during and after RT followed by oral valproic acid as maintenance therapy (a histone deacetylase/HDAC inhibitor) 1 ; and HIT-GBM-D, a pilot phase II study, evaluated the efficacy of single-agent methotrexate (MTX) prior to RT and chemotherapy. 22 In this pilot study, 2 doses of MTX (5 gm/m 2 ) were given prior to RT followed by simultaneous chemotherapy-RT and subsequent maintenance chemotherapy as per the HIT-GBM-C protocol. The toxicity profile was acceptable, with no deaths related to drug toxicity.…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…19 HIT-GBM-B -treated participants with RT and concurrent chemotherapy (cisplatin/etoposide in the first cycle and cisplatin/ etoposide/ifosfamide in the second cycle) followed by interferon-g and/or low-dose cyclophosphamide maintenance therapy 20 ; HIT-GBM-C involved administration of intensive chemotherapy (vincristine, cisplatin, ifosfamide, and etoposide) both during and after RT followed by oral valproic acid as maintenance therapy (a histone deacetylase/HDAC inhibitor) 1 ; and HIT-GBM-D, a pilot phase II study, evaluated the efficacy of single-agent methotrexate (MTX) prior to RT and chemotherapy. 22 In this pilot study, 2 doses of MTX (5 gm/m 2 ) were given prior to RT followed by simultaneous chemotherapy-RT and subsequent maintenance chemotherapy as per the HIT-GBM-C protocol. The toxicity profile was acceptable, with no deaths related to drug toxicity.…”
Section: Chemotherapymentioning
confidence: 99%
“…Data from this study suggested that the HIT-GBM-D protocol is favorable for treating pHGG patients with a GTR. 22 The approach of giving 2 cycles of high-dose MTX prior to radiochemotherapy will be assessed in a phase III RCT, and results from the randomized study are pending. The German Society for Pediatric Oncology Vanan and Eisenstat: "Management of pediatric high-grade gliomas" conducted a randomized clinical trial to evaluate the efficacy of pre-RT intensive chemotherapy in pHGGs in 1991.…”
Section: Chemotherapymentioning
confidence: 99%
“…MTX is a folate antagonist with limited uptake in the brain, which likely contributes to the need for high-dose therapy (Nierenberg et al, 1991;Wolff et al, 2011). Studies in rodents (Devineni et al, 1996) and patients (Blakeley et al, 2009) that used brain microdialysis to measure the brain interstitial fluid MTX concentrations attest to its limited distribution in the normal brain, with a brain-to-plasma ratio 0.051 6 0.032 and 0.032 6 0.094 in rodents and humans, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Hiçbiri YDG olgularına anlamlı bir yarar getirmemiştir. [14][15][16] Fransa Pediatrik Onkoloji Grubu da, 1990-1996 arasında RT öncesi verilen karmustin (BCNU), sisplatin ve etoposid (VP-16) (BCV) tedavisinin etkinliğini araştırmış ancak pulmoner toksisitesi çok fazla görülen bu KT seçeneği önerilmemiştir. [17] Erişkin GBM'li hastalarda Temozolomide'nin (TMZ) etkinliği gösterildikten sonra, birçok pediatrik çalışma bu tedavi protokolünü denemiş ancak benzer yaşam sürelerini gösterememiştir.…”
Section: Yüksek Dereceli Gliom Tedavisiunclassified